The Iraqi Deputies’ Stance on the Privilege of the Hejaz Railway in the Discussions of the Ottoman Council of Deputies 1908-1914 CE - Alwan, Ass.Prof Dr. Rasha Jameel; Abdul Sada, Ass.Lecture Widad (Thi Qar Arts Journal, 2023)
The Hejaz Railway, one of the most significant projects undertaken by the Ottoman Empire during the reign of Sultan Abdul Hamid II, stands as a remarkable accomplishment. It was a collaborative effort involving Arabs and Muslims from various Ottoman provinces, including Iraq. Their contributions were vital due to the railway's religious, political, economic, and military significance. Consequently, the Hejaz Railway garnered attention during the discussions of the Ottoman Council of Deputies from 1908 to 1914, where Iraqi deputies actively participated with their proposals and opinions.The research delves into the Hejaz Railway project, which received foreign privileges granted to its German ally by the Ottoman Empire. Despite differing perspectives among Arab and Turkish writers regarding the concept and motivations behind these privileges, the railway sparked numerous debates within the Ottoman Council of Deputies. These discussions highlighted the divergence of views between Arabs and Ottomans concerning the railway project.As the Ottoman Empire shifted its policies toward European nations, it sought to strengthen relations through alliances and agreements known as "privileges." These privileges encompassed economic, military, political, and religious aspects, granting European powers freedom of movement and trade within the Ottoman territories. However, this approach had unintended consequences, as these privileges became tools for European intervention in the empire's internal affairs and control over its economy. Notably, the Hejaz Railway privilege was bestowed during Sultan Abdul Hamid II's rule.The Hejaz region held immense importance within the Ottoman Empire due to its status as the starting point of the Islamic world. Geographically and religiously, the Hejaz was unique, maintaining a special position for the Ottomans. This situation persisted for centuries until the Hejaz separated from Ottoman rule after the Great Arab Revolt. Consequently, the Hejaz Railway project garnered widespread Islamic interest.